Minnesota Policy on Pharmacist-Prescribed Contraceptives: Benefits, Limitations, and Opportunities for Improvement - Federico Facciolo; Joel Farley (University of Minnesota Libraries Publishing, 2021)
In August 2020, pharmacists were authorized to prescribe contraceptives in Minnesota outside of a collaborative practice agreement. To practice under this new authorization, pharmacists must complete formal contraceptive prescribing training and follow guidelines which include restrictions on patient's age and appropriate screening and assessment requirements. Allowing pharmacists to prescribe contraceptives has the potential to extend contraceptive access, decrease overall health care costs, and improve outcomes. However, barriers to the expansion of contraceptive prescribing by pharmacists may prevent widespread adoption of this practice in Minnesota. A key concern among pharmacists is a lack of reimbursement for providing this service.  Other states adopting contraceptive prescribing by pharmacists which have not paid for this service have reported limited implementation and discontinuation of this service. To improve contraceptive access to Minnesotans, policymakers should consider expanding provider status to pharmacists and providing reimbursement to pharmacists for contraceptive services.